Targeted Photodynamic Therapy Using Alloyed Nanoparticle-Conjugated 5-Aminolevulinic Acid for Breast Cancer - Hanieh Montaseri; Cherie Ann Kruger; Heidi Abrahamse (MDPI AG, 2021)
Photodynamic therapy (PDT) has been investigated as an effective, non-invasive, and alternative tumor-ablative therapy that uses photosensitizers (PSs) and safe irradiation light in the presence of oxygen to generate reactive oxygen species (ROS) to kill malignant cancer cells. However, the off-target activation of the PSs can hinder effective PDT. Therefore, an advanced drug delivery system is required to selectively deliver the PS to the therapeutic region only and reduce off-target side effects in cancer treatment. The integration of laser-initiated PDT with nanotechnology has provided new opportunities in cancer therapy. In this study, plasmonic bimetallic nanoparticles (NPs) were prepared for the targeted PDT (TPDT) of in vitro cultured MCF-7 breast cancer cells. The NPs were functionalized with PEG through Au-thiol linkage to enhance their biocompatibility and subsequently attached to the PS precursor 5-aminolevulinic acid via electrostatic interactions. In order to enhance specific targeting, anti-HER-2 antibodies (Ab) were decorated onto the surface of the nanoconjugate (NC) to fabricate a 5-ALA/Au-Ag-PEG-Ab NC. In vitro studies showed that the synthesized NC can enter MCF-7 cells and localize in the cytoplasm to metabolize 5-ALA to protoporphyrin IX (PpIX). Upon light irradiation, PpIX can efficiently produce ROS for the PDT treatment of MCF-7. Cellular viability studies showed a decrease from 49.8% ± 5.6 ** to 13.8% ± 2.0 *** for free 5-ALA versus the NC, respectively, under equivalent concentrations of the PS (0.5 mM, IC50). These results suggest that the active targeted NC platform has an improved PDT effect on MCF-7 breast cancer cells.